Zirconium Phosphate Supported on g-C3N4 Nanocomposite for Sensitive Detection of Nitrite. Issue 8 (4th August 2021) - Sriram, Balasubramanian; Baby, Jeena N.; Hsu, Yung-Fu; Wang, Sea-Fue; George, Mary
Abstract : Food protection and preservation aims to prevent spoilage and contamination, which can improve consumer health, but prolonged and excessive consumption of food preservatives can cause serious health risks. Nitrite (NO2 − ) anion, a widely used food preservative, is associated with possible carcinogenic effects in prolonged exposures that require the implementation and identification of methods for immediate quantification. In this sense, hierarchical nanostructured materials have enormous material advancement potential that can be applied to real-time analysis of undesirable ions. The ordered geometric arrangement and multiple components of these structures offer synergistic effects, increased active surface area, and multiple functionalities, outperforming their bulk counterparts and enhancing various properties. The present work deals with the synthesis of α -zirconium phosphate ( α -ZrP) that is composited with graphitic carbon nitride (CN) via ultrasonication for the electrochemical determination of NO2 − . The facile ion-exchange capability of the former inorganic layered compound can effectively manage the disposition of NO2 −, which is further accelerated by the interspersing of a carbonaceous material such as CN. The sensing capacity of the nanocomposite shows comprehensive response ranges, high selectivity and sensitivity towards NO2 − detection that allows the fabrication of real-time analysers based on ion-exchange materials for the remediation of environmental contaminants.